Anti-SLAPP and pro-women a study on the applicability of the concept of strategic lawsuit against public participation to cases involving violence against women and their children (2022)
Domestic abuse, particularly those committed against women, is not an uncommon topic in Filipino households. To address this problem, Congress has passed Republic Act No. 9262, or the Anti-Violence Against Women and Their Children Act of 2004 ("Anti-VAWC Act"). Since the passing of this landmark legislation, women have had an easier reporting the abuse and violence committed against them; over the years, however, we have seen that this law no longer suffices. As a response to the many women speaking up about their abuse, the abusers themselves have found a way to use the justice system against the survivors by filing baseless and costly cases, often defamation suits, against these women-survivors, with the goal of silencing them. Given this change in circumstance, our laws should likewise adapt and provide swomen-survivors with more remedies than before. One way to do this is by making the concept of Strategic Lawsuit Against Public Participation ("SLAPP") applicable to violence against women and their children ("VAWC") cases, both substantively and procedurally. This Article argues that SLAPP as a concept should be made applicable to VAWC-related cases in two ways-firs, substantively, as a cause of action for filing a case under the Anti- VAWC Act, and second, procedurally, as a defense that may be
interposed within the very same case filed against them.
Keywords: Strategic lawsuits against public participation; Anti-Violence Against Women and Their Children Act of 2004 -- Jurisprudence